2007
DOI: 10.4049/jimmunol.179.11.7959
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Chromatin and Nuclear Fragmentation In Vivo Impairs the Production of Lupus Anti-Nuclear Antibodies

Abstract: Nuclear autoantigens in systemic lupus erythematosus are thought to derive primarily from apoptotic cells, yet there is no direct evidence that interfering with apoptosis impairs the generation of lupus autoantibodies. Here we use a mouse model that lacks the endonuclease caspase-activated DNase (CAD), resulting in an absence of chromatin and nuclear fragmentation during apoptotic cell death. We show that in this mouse, production and release into circulation of chromatin is impaired after exposure to several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…For example, similar in situ exposure and retention of large un-fragmented chromatin fragments have been described in several experimental nuclease deficiencies on non-autoimmune backgrounds (see e.g. [9], [59][61]). The clinical consequence of chromatin fragments in these experimental nuclease deficiencies differ from that in kidneys of individuals with lupus nephritis, simply because in the latter, antibodies to chromatin are present.…”
Section: Discussionmentioning
confidence: 59%
“…For example, similar in situ exposure and retention of large un-fragmented chromatin fragments have been described in several experimental nuclease deficiencies on non-autoimmune backgrounds (see e.g. [9], [59][61]). The clinical consequence of chromatin fragments in these experimental nuclease deficiencies differ from that in kidneys of individuals with lupus nephritis, simply because in the latter, antibodies to chromatin are present.…”
Section: Discussionmentioning
confidence: 59%
“…In addition, DFF null mice do not develop SLE. By contrast however, in a pristine-induced animal model for SLE, DFF null mice produce significantly lower levels of antibodies to chromatin, small nuclear ribonucleoprotein particles and to other nuclear components, when compared to control wild type mice, but produce normal levels of autoantibodies to cytoplasmic components [105]. It can be concluded from these results that DFF may contribute to the susceptibility to acquire SLE.…”
Section: Dff and Susceptibility To Systemic Lupus Erythematosusmentioning
confidence: 73%
“…[20]. Furthermore, when DFF null mice are challenged with specific antigens, they mount a normal immune response [105]. In addition, DFF null mice do not develop SLE.…”
Section: Dff and Susceptibility To Systemic Lupus Erythematosusmentioning
confidence: 99%
“…Coligation of additional receptors for DAMPs instead appears to be required. Research in the field of autoimmunity has convincingly shown that dying cell-derived nucleosomal material is very potent in this regard (Frisoni et al, 2007; Urbonaviciute et al, 2008). Hence, interfering with DNase II activity, which in phagocytes mediates the proper degradation of engulfed prey cell DNA, could represent a promising strategy to stimulate the described IFN cascade required for the induction of productive immune responses and well-known for its crucial role in the etiopathogenesis of autoimmune diseases, such as SLE (Kawane et al, 2006; Marshak-Rothstein, 2006; Deng and Tsao, 2010).…”
Section: Dying Cell Clearance and The Induction Of Anti-tumor Immune mentioning
confidence: 99%